2021
DOI: 10.1016/j.ssmph.2021.100773
|View full text |Cite
|
Sign up to set email alerts
|

Women's autonomy in household decision-making and safer sex negotiation in sub-Saharan Africa: An analysis of data from 27 Demographic and Health Surveys

Abstract: Women's ability to negotiate the conditions and timing of sex is key to several reproductive health outcomes including family planning and prevention of sexually transmitted infections. We investigated the association between women's autonomy in household decision-making and safer sex negotiation (SSN) in sub-Saharan Africa (SSA). This was a cross-sectional analysis of data from the Demographic and Health Survey (DHS) of 27 countries in SSA. Data were analyzed using Stata version 16.0 using descriptive statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 23 publications
11
51
0
Order By: Relevance
“…We found a 71.6% prevalence of safer sex negotiation among women in sexual unions in SSA. The high prevalence of safer sex negotiation found in this study corroborates the findings of previous studies that found the prevalence of safer sex negotiation to be 77.1% [30] and 83.4% [31] respectively. There were country level variations in the prevalence of safer sex negotiation among women in sexual unions in SSA.…”
Section: Discussionsupporting
confidence: 91%
“…We found a 71.6% prevalence of safer sex negotiation among women in sexual unions in SSA. The high prevalence of safer sex negotiation found in this study corroborates the findings of previous studies that found the prevalence of safer sex negotiation to be 77.1% [30] and 83.4% [31] respectively. There were country level variations in the prevalence of safer sex negotiation among women in sexual unions in SSA.…”
Section: Discussionsupporting
confidence: 91%
“…With regard to safer sex negotiation, 82.7% of the women surveyed had the capacity to negotiate for safer sex. Similar studies in SSA have reported a high prevalence of safer sex negotiation among women in SSA (Aboagye et al, 2021;Seidu et al, 2021). The increasing prevalence of safer sex negotiation among women in SSA could be due to factors such as improved access to education and mass media exposure (Aboagye et al, 2021;Seidu et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…Women who responded 'yes' for at least one of the two variables were said to have safer sex negotiations, and those that responded 'no' for both variables were categorized as not having safer sex negotiation. This categorization was informed by previous studies that used the DHS dataset (Darteh et al, 2019;Tenkorang, 2012;Sano et al, 2018a;Putra et al, 2020;Budu et al, 2021;Seidu et al, 2021).…”
Section: Independent Variablementioning
confidence: 99%
See 2 more Smart Citations